(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
–This study aims to examine the kinship between Banyumasan Javanese and Palembang Alus, which are part of the Austronesian language family. This research describes the percentage of kinship and separation time between Banyumasan Javanese and Palembang Alus using lexicostatistical and glottochronological methods. In addition, this research also explains the form of kinship between Banyumasan Javanese and Palembang Alus. The data used in this study is a list of 200 basic Swadesh vocabulary words collected from native speakers of both languages. Out of the 200 vocabulary words, 83 words are related with a percentage level of kinship of 41.5%. The results of this study show that these two languages separated between 2209 - 1841 years ago or around 184 BC - 184 AD calculated from the present time (2025). Based on this analysis, it can be concluded that the two languages are related at the family level.